Culturing of Giardia lamblia under microaerobic conditions can impact metronidazole susceptibility by inducing increased expression of antioxidant enzymes - Kateryna Starynets; Ana Paunkov; Anja Wagner; Klaus Kratochwill; Christian Klotz; David Leitsch (International Journal for Parasitology: Drugs and Drug Resistance)
The microaerophilic/anaerobic protist Giardia lamblia is a world-wide occurring parasite of the human small intestine. It causes giardiasis which manifests as diarrhoea accompanied by other sequelae. Giardiasis is most commonly treated with either the 5-nitroimidazole metronidazole or the benzimidazole albendazole. Unfortunately, the number of refractory cases is increasing, which is probably caused, at least in part, by drug resistance. However, most attempts to isolate metronidazole-resistant G. lamblia strains from patients have failed so far because the parasites were not resistant when tested in vitro.We hypothesized that this failure might be caused by drug assay conditions which are standardly anaerobic, and performed metronidazole susceptibility testing with two well studied strains, i.e. WB C6 and BRIS/87/HEPU/713 (strain 713) under microaerophilic conditions. Indeed, 713 proved to be less susceptible to metronidazole under microaerophilic conditions as compared to anaerobic conditions, and residual growth was even noted at concentrations of metronidazole similar to those in the serum of treated patients (i.e. about 100 μM). Further experiments showed that 713 also grows much faster under microaerobic conditions than WB C6. Reduced susceptibility to metronidazole under microaerobic conditions was also observed in a clinical isolate from a refractory giardiasis case.Two-dimensional gel electrophoresis showed that microaerobic growth was accompanied by the upregulation of superoxide reductase, a pyridoxamine 5′-phosphate oxidase putative domain-containing protein, and a TlpA-like protein in 713 but not in WB C6. All three proteins are known, or can be predicted to have antioxidant functions. Indeed, overexpression of pyridoxamine 5′-phosphate oxidase in WB C6 from a plasmid carrying the respective gene behind the arginine deiminase promoter significantly improved growth of the transfected cell line under microaerobic conditions. Moreover, similarly overexpressed superoxide reductase conferred significant protection against metronidazole.Our results suggest that oxygen concentrations can affect the outcomes of metronidazole treatment against G. lamblia.